SOCIAL EMOTIONAL LEARNING AND LEARNING MOTIVATION ON SOCIAL EMPATHY AND STUDENT LEARNING OUTCOMES IN SOCIAL STUDIES SUBJECTS IN ELEMENTARY SCHOOLS - Wawan Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the social emotional learning model compared to conventional methods and its interaction with learning motivation on social empathy and learning outcomes of elementary school students in Social Studies (IPS). This study uses a quantitative approach with a quasi-experimental design with a 2x2 factorial model. The population in this study were all fifth-grade students at SD Negeri Kelurahan Menanggal Surabaya, totaling 250 students, with a sample size of 120 students spread across four classes (ABCD) and selected using a purposive sampling technique. The instruments used included a questionnaire to measure learning motivation and social empathy and a learning achievement test to measure mastery of the IPS material. Data collection techniques were carried out through distributing questionnaires and conducting written tests. Data were analyzed using the Multivariate Analysis of Variance (MANOVA) technique with the help of SPSS software version 27.00. The results showed that there was a significant influence of the learning model on social empathy and students' IPS learning outcomes. Social emotional learning was more effective than conventional methods in improving both. Learning motivation also had a significant effect on social empathy and learning outcomes. Furthermore, there was a significant interaction between the learning model and learning motivation on both dependent variables. This interaction indicates that social-emotional learning has a greater impact, especially on students with low motivation. The conclusion of this study is that the implementation of social-emotional learning in social studies is highly effective in building social empathy and improving students' academic achievement, especially when combined with efforts to increase learning motivation.